Developing the Knowledge and Mentoring Skills of Future Special Education Leaders. (December 2022) - Ortogero, Shawna P.; Barcarse, Tierney O.; Ray, Amber B.
To curb the negative impact that rural Hawaii's qualified special education teacher (SET) shortage has on students with disabilities, a professional development (PD) course was developed to examine the effect the program had on mentoring beginning SETs. Course programming was aligned to SET preparation coursework, targeted at the ongoing PD needs of beginning rural SETs, in addition to being grounded in the literature on special education teacher retention and Tichy's (1983) Technical, Political, and Cultural Dynamics Theory. Seven licensed educators and their mentees participated in the course. Data were collected using surveys, knowledge assessment, culminating reflections, and course evaluations. Participants were satisfied with the course and found mentoring and instructional practices beneficial. The course had a positive impact on the overall knowledge of participants. Nearly all mentees discussed that coaching helped them grow as a teacher and resulted in lessons where students were more successful. Implications for practice are discussed.